2002
DOI: 10.1016/s0924-9338(02)80880-x
|View full text |Cite
|
Sign up to set email alerts
|

Time perspective in suicide attempters

Abstract: Suicide in mental health service users diagnosed with schizophrenia Time experience is related to mental health as well as to personality traits like impulsivity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…One study reported that depressive symptomatic individuals with future TP predominance had a lower suicidal tendency than non-dominant individuals [ 17 ]. It has been shown that past negative TP and present fatalistic TP scores of individuals with severe suicidal ideation and who have attempted suicide are significantly higher [ 18 , 19 ]. In contrast, those with lower future TP and present hedonistic TP scores have more severe suicidal ideation [ 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…One study reported that depressive symptomatic individuals with future TP predominance had a lower suicidal tendency than non-dominant individuals [ 17 ]. It has been shown that past negative TP and present fatalistic TP scores of individuals with severe suicidal ideation and who have attempted suicide are significantly higher [ 18 , 19 ]. In contrast, those with lower future TP and present hedonistic TP scores have more severe suicidal ideation [ 20 ].…”
Section: Introductionmentioning
confidence: 99%